The Relationship between Adverse Childhood Experiences (ACE) and Juvenile Offending Trajectories in a Juvenile Offender Sample. Issue 3 (May 2015) - Baglivio, Michael T.; Wolff, Kevin T.; Piquero, Alex R.; Epps, Nathan
Abstract Purpose Adverse childhood experiences have been identified as a key risk factor for offending and victimization, respectively. At the same time, the extent to which such experiences distinguish between unique groups of offenders who vary in their longitudinal offending patterns remains an open question, one that is pertinent to both theoretical and policy-related issues. This study examines the relationship between adverse childhood experiences for distinguishing offending patterns through late adolescence in a large sample of adjudicated juvenile offenders. Methods The current study uses data from 64, 000 adjudicated juvenile offenders in the State of Florida. We use Semi-Parametric Group-Based Method (SPGM) to identify different latent groups of official offending trajectories based on individual variation over time from ages 7 to 17. Multinomial logistic regression was used to examine which measures, including the ACE score, distinguished between trajectory groups. Results Findings indicate five latent trajectory offending groups of offending through age 17 and that increased exposure to multiple Adverse Childhood Experiences distinguishes early-onset and chronic offending from other patterns of offending, net of several controls across demographic, individual risk, familial risk, and personal history domains. Conclusions Childhood maltreatment as measured by the cumulative stressor Adverse Childhood Experiences score influences official offending trajectories.